Research of Client Level Framework for SaaS Software Service Based on Mass Customization - Qinglie Wu; Xiaoli Luo (Dianxin kexue)
Mass customization is the key to the successful implementation of SaaS software service. In this paper, in order to meet diverse requirements of different tenants in the system interface, and to visit application software through all kinds of terminal, a client level framework for SaaS software service based on mass customization is proposed. In which, XML document describes the detailed requirements for the application system interface. According to this, the interface configuration algorithm is designed to produce data, which interacts with the terminal components to create user interface for tenants. Finally an example demonstrates the feasibility of this framework.